The effect of digitalization transformation on greenwashing of Chinese listed companies: an analysis from the dual perspectives of resource-based view and legitimacy - Zhang, Kesen; Pan, Zhen; Zhang, Keming; Ji, Feng (Frontiers in Environmental Science, 2023)
Whether digital transformation (DIT) can curb greenwashing behavior is a topic worth discussing. To fill this gap, this paper empirically discusses the effect of DIT on greenwashing, and further discusses how government subsidies, resource slack, and external pressure affect them. The findings are as follows: (1) DIT has an inhibitory effect on greenwashing. (2) Government subsidies, resource slack, and public pressure positively moderate the relationship. (3) The main effect of DIT does inhibit symbolic behavior, but the impact on substantive behavior is not obvious. The moderating effects of various variables are also different.